Acanthopanax trifoliatus inhibits lipopolysaccharide‐induced inflammatory response in vitro and in vivo. Issue 10 (10th September 2015) - Chien, Tzu‐Mei; Hsieh, Po‐Chow; Huang, Shyh‐Shyun; Deng, Jeng‐Shyan; Ho, Yu‐Ling; Chang, Yuan‐Shiun; Huang, Guan‐Jhong
Abstract: Acanthopanax trifoliatus is a well‐known herb that is used for the treatment of bruising, neuralgia, impotence, and gout in Taiwan. This herb exhibits multifunctional activities, including anticancer, anti‐inflammation, and antioxidant effects. This paper investigated the in vitro and in vivo anti‐inflammatory effect of A. trifoliatus . High‐performance liquid chromatography analysis established the fingerprint chromatogram of the ethyl acetate fraction of A. trifoliatus (EAAT). The anti‐inflammatory effect of EAAT was detected using lipopolysaccharide (LPS) stimulation of the mouse macrophage cell line RAW264.7 in vitro and LPS‐induced lung injury in vivo . The effects of EAAT on LPS‐induced production of inflammatory mediators in RAW264.7 murine macrophages and the mouse model were measured using enzyme‐linked immunosorbent assay and Western blot. EAAT attenuated the production of LPS‐induced nitric oxide (NO), tumor necrosis factor‐alpha, interleukin‐1β (IL‐1β), and IL‐6 in vitro and in vivo . Pretreatment with EAAT markedly reduced LPS‐induced histological alterations in lung tissues. Furthermore, EAAT significantly reduced the number of total cells and protein concentration levels in the bronchoalveolar lavage fluid. Western blotting test results revealed that EAAT blocked protein expression of inducible NO synthase, cyclooxygenase‐2, phosphorylation of Nuclear factor‐kappa‐B Inhibitor alpha (IκB‐α) protein, and mitogen‐activated protein kinases in LPS‐stimulated RAW264.7 cells as well as LPS‐induced lung injury. This study suggests that A. trifoliatus may be a potential therapeutic candidate for the treatment of inflammatory diseases.